2023
DOI: 10.3389/fpsyt.2023.1201863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercise on non-suicidal self-injury in adolescents: the chain mediating role of perceived social support and self-concept

Haoran Yu,
Qinglei Mu,
Ke Li

Abstract: ObjectiveTo study the effect of physical exercise on non-suicidal self-injury in adolescents and to verify the chain mediating role of perceived social support and self-concept. Methods: A survey study was conducted on 1,426 adolescents in Chengdu, Sichuan Province. A chain mediation model was used to verify whether perceived social support and self-concept played a mediating role.ResultsPhysical exercise was significantly negatively associated with non-suicidal self-injury in adolescents (β = −0.53, p &lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The results of the correlation analyses in this study showed that there was a significant positive correlation between physical activity and perceived social support among college students, thereby supporting the Hypothesis 1. The results of this study are consistent with previous findings (Yu et al, 2023). Engaging in regular physical activities contributes to improved physical strength and health among college students (Moylan et al, 2022; Shu et al, 2023), enhancing their self‐esteem and fostering confidence and positive attitudes in their daily lives (Baikoğlu et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…The results of the correlation analyses in this study showed that there was a significant positive correlation between physical activity and perceived social support among college students, thereby supporting the Hypothesis 1. The results of this study are consistent with previous findings (Yu et al, 2023). Engaging in regular physical activities contributes to improved physical strength and health among college students (Moylan et al, 2022; Shu et al, 2023), enhancing their self‐esteem and fostering confidence and positive attitudes in their daily lives (Baikoğlu et al, 2019).…”
Section: Discussionsupporting
confidence: 94%